Economic evaluation of induction motor based on motor’s nameplate data and initial cost - Mohammed Baniyounis; Ayamn Agha; Hudefah Al-kashashneh; Abdullah Al-Omoush (Institute of Advanced Engineering and Science, 2022)
This paper presents a practical approach to calculate the total owning cost (TOC) of a three-phase Induction Motor, which is based on the motor’s nameplate data and the purchasing price. The economic evaluation is performed considering both the induction motor electrical energy losses and its amortized annual capital cost. The proposed technique consists of three stages, where the total power losses are determined analytically in the first stage. The load loss factor (LSF) is statistically obtained to determine the total energy losses in the second stage. In the third stage, the economic evaluation was conducted. The obtained results show that the proposed approach is a helpful tool for the decision-maker when comparing the received offers from different vendors and finding the answer to the question of which offer has less TOC. Finally, the proposed method is illustrated through a numerical example and software using MATLAB was performed. Results and conclusions have been summarized and discussed.